PENGARUH PERBEDAAN METODE EKSTRAKSI TERHADAP KADAR POLIFENOL DAUN TEH PUTIH (Camellia sinensis) - Anita, Anita Khairunnisa (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2024)
Extraction methods play an important role in determining the polyphenol content of white tea (Camellia sinensis) leaves, which have high antioxidant properties. This study aims to compare the efficiency of several extraction methods, including Multistage Maceration, Microwave-Assisted Extraction (MAE), and Ultrasonic-Assisted Extraction (UAE), in producing optimal polyphenol levels. Extraction was performed using 96% ethanol solvent with specific parameters for each method. Determination of polyphenol content was done by Folin-Ciocalteu method using UV-Vis spectrophotometer at 765 nm wavelength. The results showed that the MAE method produced the highest polyphenol content, at 63.60%, compared to UAE (48.35%) and Graded Maceration (lower). The advantages of MAE include efficient extraction time, less solvent usage, and higher extract yield. This study highlights the importance of choosing the right extraction method to enhance the health benefits of white tea through its polyphenol content.